Identity‐based motivation: Implications for action‐readiness, procedural‐readiness, and consumer behavior - Oyserman, Daphna (Journal of Consumer Psychology, 2009)
AbstractChoices are often identity‐based but the linkage to identity is not necessarily explicit or obvious for a number of reasons. First, identities feel stable but are highly sensitive to situational cues. Second, identities include not only content but also readiness to act and to use procedures congruent with the identity. Third, identities can be subtly cued without conscious awareness. Fourth, what an accessible identity means is dynamically constructed in the particular context in which it is cued. Because identities carry action‐ and procedural‐readiness, the outcome of an identity‐based motivation process may be similar to or different from the choices an individual would have made in another setting. Moreover, once an identity is formed, action and procedural‐readiness can be cued without conscious awareness or systematic processing, resulting in beneficial or iatrogenic outcomes.